Spectrofluorimetric Determination of Coumarin in Commercial Tablets - Marcolan, Mirian; Martins, Priscila Alfonso; Pedrosa, Valber A. [UNESP]; Rodrigues, Maira R.; de Oliveira, Hueder P. M.; Codognoto, Lucia (Springer/plenum Publishers, 2011)
A simple, rapid and effective analytical method based on fluorescence spectroscopy for the determination of coumarin in pharmaceutical formulations without pre-treatment or pre-concentration step was development. Coumarin had maximum excitation and emission at 310 nm and 390 nm, respectively. Optimum conditions for the detection of coumarin were investigated. Under optimized conditions, we observed a linear behavior for the sign of coumarin in the concentration range of 2.5 x 10(-6) to 1.0 x 10(-4) mol L(-1), with linearity of 0.998 and sensitivity of 2.9 x 10(10) u.a/mol L(-1). The proposed method was validated in terms of accuracy, precision and specificity of coumarin using the standard addition and external calibration. It was noted that the results support (P < 0.05), indicating that the matrices were not an interference in the determination of coumarin by fluorescence spectroscopy. The results were favorable compared with those obtained by reference chromatographic methods.
Keywords: Coumarin; Fluorescence spectroscopy; Pharmaceutical preparations